background image

3.7. INFINITE ASSOCIATIVITY AND ORDINATED PRODUCT

47

Proof.

Let

R

=

n

d

A

X

X

P

S

o

. Then for every

X, Y

P

S

A

l

X

u

A

A

l

Y

=

A

l

((

X

Y

)

(

X

\

Y

))

u

A

A

l

Y

=

 

A

l

(

X

Y

)

t

A

A

l

(

X

\

Y

)

!

u

A

A

l

Y

=

 

A

l

(

X

Y

)

u

A

A

l

Y

!

t

A

 

A

l

(

X

\

Y

)

u

A

A

l

Y

!

=

 

A

l

(

X

Y

)

u

A

A

l

Y

!

t

A

A

=

A

l

(

X

Y

)

u

A

A

l

Y.

Applying the formula

d

A

X

u

A

d

A

Y

=

d

A

(

X

Y

)

u

A

d

A

Y

twice we get

A

l

X

u

A

A

l

Y

=

A

l

(

X

Y

)

u

A

A

l

(

Y

(

X

Y

)) =

A

l

(

X

Y

)

u

A

A

l

(

X

Y

) =

A

l

(

X

Y

)

.

But for any

A, B

R

there exist

X, Y

P

S

such that

A

=

d

A

X

,

B

=

d

A

Y

.

So

A

u

A

B

=

d

A

X

u

d

A

Y

=

d

A

(

X

Y

)

R

.

3.6. A proposition about binary relations

Proposition

280

.

Let

f

,

g

,

h

be binary relations. Then

g

f

6

h

g

6

h

f

1

.

Proof.

g

f

6

h

a, c

:

a

((

g

f

)

h

)

c

a, c

: (

a

(

g

f

)

c

a h c

)

a, b, c

: (

a f b

b g c

a h c

)

b, c

: (

b g c

b

(

h

f

1

)

c

)

b, c

:

b

(

g

(

h

f

1

))

c

g

6

h

f

1

.

3.7. Infinite associativity and ordinated product

3.7.1. Introduction.

We will consider some function

f

which takes an arbi-

trary ordinal number of arguments. That is

f

can be taken for arbitrary (small,

if to be precise) ordinal number of arguments. More formally: Let

x

=

x

i

n

be a